Chitosan-coated Liposomes of Centella asiatica Extract: An In vitro Formulation Design for Oral Delivery - Dubey, Dr. Akhilesh (Asian Journal of Pharmaceutics (AJP), 2020)
Aim: A chitosan-coated liposomes of standardized Centella asiatica extract (CAE) was developed with the aim of improving the solubility of its phytoconstituents for the oral route with the intention to treat Alzheimer’s disease. Materials and Methods: The CAE was obtained by the soxhletion process. The formulation was optimized using design-expert software, solvent evaporation, and ionotropic gelation method was adopted to prepare CAE liposome (CAEL) and chitosan-coated CAE liposomes (CCAEL), respectively. The prepared CCAEL was characterized for its vesicle size, entrapment efficiency, polydispersity index, drug content analysis, Fourier transform infrared (FTIR), differential scanning calorimetry (DSC), transmission electron microscopy (TEM), atomic force microscopy (AFM), in vitro drug release, in vitro antioxidant study, ex vivo permeation study, and stability study. Results and Discussion: The proper amalgamation of drug and chitosan-phospholipid mixture was confirmed by FTIR and DSC. The surface morphology of the prepared formulation was examined by TEM and AFM. The in vitro rate of drug release pattern was analyzed where CAE showed less rate of release of 35.34 ± 0.30% in about 10 h due to poor solubility, while approximately 58.6 ± 0.42% release was observed from optimized CCAEL. In vitro antioxidant study demonstrated that free radical scavenging activity of CAE was retained even after intricate it with the phospholipid, that is, % inhibition of 2,2-diphenyl-1-picrylhydrazyl at 50 μg/ml was found 73.84% whereas 74.4% CAE. In vitro intestinal study proved that the permeation rate increases due to the encapsulation of chitosan-phospholipid complex. Stability study showed that chitosan coated liposomes were stable due to compact chitosan coating layer. Conclusion: The outcome of the current study is quite encouraging, shows better solubility and permeability. Further detailed preclinical studies are required to be conducted to ensure better product development.